Edgar Allen Poe : a phenomenological view - Halliburton, David (Princeton legacy library., 1973)
By attempting to suspend moral, ideological, or psychological assumptions, a phenomenological interpretation of literature hopes to reach ""the things themselves, "" the essential phenomena of being, space, and time, as they are constituted, by consciousness, in words. Although there has been a tradition of phenomenological criticism in Europe for the last twenty years, David Halliburton is the first to write a general study of an American author from this particular point of view. The book begins with a methodological chapter that sets out the assumptions and procedures of the approach. This.